Analisa Gangguan Muskuloskeletal Pada Pegawai Laundry Di Sekitar Kampus Universitas Muhammadiyah Surakarta - Nasrullah, Fendyahya Giffari, Wahyuni, SST.Ft., M.kes (2017)
Background: One informal industries that have potential hazards musculoskeletal complaints are in an occupational activity is domestic laundry industry. Currently the household laundry industry is growing rapidly and can be found easily in the city - a big city. Formerly laundry business usually only in hotels but now has become a business opportunity for the community.Objective: To determine the type of musculoskeletal disorders in the laundry employees around the university campus of Muhammadiyah Surakarta.Methods: This type of research merpakan observational research by using descriptive analytic. This study using cross sectional study design, Result: note that the most widely perceived laundry employees around the campus is different - different complaints are often felt in the laundry employee is an employee of the neck as much as 19 bar (36.5%), nape there are 13 people (26%) left shoulder laundry as many as 19 employees (36.5%), the right shoulder as much as 25 laundry employees (48.0%), left upper arm there are eight people (16%), back there are 13 people (26%), right upper arm 11 people (22%), the waist as many as 27 people (46.2%), hip 24 people (48%), right wrist there are 10 people (20%), the right hand there are 10 people (20%), the left leg is no 10 people (20%), right leg No 11 people (22%).Conclusion: In the laundry employees are musculoskeletal disorders and any employee complaints laundry is different - different but most in the laundry employees complain about the neck as much (36.5%), the left shoulder as much (36.5%), the right shoulder as many (48, 0%), back as many (26.0%) and waist as much (46.2%).